Fluoride and trimetaphosphate association as a novel approach for remineralization and antiproteolytic activity in dentin tissue - Nunes, Gabriel Pereira [UNESP]; Danelon, Marcelle [UNESP]; Pessan, Juliano Pelim [UNESP]; Capalbo, Letícia Cabrera [UNESP]; Junior, Nilson Antônio Nunes [UNESP]; Matos, Adriana Arruda [UNESP]; Souza, José Antonio Santos [UNESP]; Buzalaf, Marília Afonso Rabelo [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP] (Elsevier, 2022)
Objective: The study evaluated the effect of solutions containing fluoride (F) and/or sodium trimetaphosphate (TMP) and F/TMP on the inhibition of MMP-2 and MMP-9, and on dentin remineralization in vitro. Design: Bovine root dentin blocks were prepared, and caries-like lesions were induced in two thirds of the surface. Blocks were then randomly divided into 13 groups/solutions (n = 10): Placebo; 0.3 %, 1 % and 3 % NaOH-hydrolyzed TMP; 0.3 %, 1 % and 3 % TMP; 250, 500 and 1100 ppm F; 250 ppm F + 0.3 % TMP; 500 ppm F + 1 % TMP and 1100 ppm F + 3 % TMP. One third of each specimen was treated with the respective solutions in pH-cycling. The mineral concentration (gHAp × cm−3 × µm) was determined by computed X-ray microtomography, and data submitted to ANOVA and Student-Newman-Keuls’ test (p < 0.05). The ability of the solutions to inhibit MMP-2 and MMP-9 activity was assessed by zymography. Results: F/TMP association led to less mineral loss in the deeper region of the lesion and reduced the depth of lesions when compared to its counterpart without TMP (p < 0.001). 3 % TMP (hydrolyzed or not), 500 ppm F and 1100 ppm F completely inhibited MMP-2 activity, while for MMP-9 such effects were only achieved by treatment with 1100 ppm F + 3 % TMP. Conclusion: Treatment with 1100 ppm F + 3 % TMP fully inhibits the gelatinolytic activity of MMPs-2 and − 9 and shows greater remineralizing capacity in artificial caries lesions in dentin. However, hydrolyzing TMP does not improve its anti-proteolytic activity and its remineralizing capacity.
Keywords: Dentin; Fluoride; Matrix metalloproteinases; Phosphate; Remineralization